Promoting Religious Moderation in the Faculty of Tarbiyah and Teacher Training at State Islamic University Kiai Haji Achmad Siddiq Jember - Mukni'ah, Mukni'ah; Rafik, Ainur; Mustajab, Mustajab (Postgraduate Program, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2023)
This article explores the implementation of the values of moderation (tawāsuṭ), equilibration (tawāzun), balance (i’tidāl), and tolerance (tasāmuḥ) at the Faculty of Tarbiyah and Teacher Training (FTIK) State Islamic University Kiai Haji Achmad Siddiq (UIN KHAS) Jember, including the role of focus group discussions. The method used in this research-based community service was qualitative research with participatory action. The results of the service showed that the effort to reinforce the values of religious moderation in the institution is implemented by organizing workshops that are open to lecturers, education staff, and students. Tawāzun values are strengthened by practicing discipline, time management, and activities as well as developing self-potential through extra and intra-campus activities. I‘tidāl values are strengthened by enforcing rules and regulations, UKT financing in accordance with the capacity and ability of students, and continuously strengthening the Ahlus Sunnah Wal Jamah learning environment. Meanwhile, tasāmuḥ values are enhanced by respecting differences of opinion and organizations. The supporting factors in efforts to strengthen the value of religious moderation at FTIK UIN KHAS Jember are support from the dean, high enthusiasm from students, lecturers, and education staff, teamwork, and the availability of supportive funds. Meanwhile, the inhibiting factor is time constraints due to signal constraints for those who join through online or Zoom meetings.